2016
DOI: 10.3762/bjoc.12.128
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cu(I)-catalyzed azide–alkyne cycloaddition for the design and synthesis of sequence specific probes targeting double-stranded DNA

Abstract: SummaryEfficient protocols based on Cu(I)-catalyzed azide–alkyne cycloaddition were developed for the synthesis of conjugates of pyrrole–imidazole polyamide minor groove binders (MGB) with fluorophores and with triplex-forming oligonucleotides (TFOs). Diverse bifunctional linkers were synthesized and used for the insertion of terminal azides or alkynes into TFOs and MGBs. The formation of stable triple helices by TFO-MGB conjugates was evaluated by gel-shift experiments. The presence of MGB in these conjugates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…MnPEGDB Is Complexed with Small Oligonucleotides (dsDNA or siRNA) for 30 min in a pH 4 Buffer a a The protonated amine group on the DMAEMA electrostatically interacts with the negative phosphates on the oligonucleotide, spontaneously forming a stable micelle with mannose presented on the corona of the polyplex. After fabrication of the MnPEGDB and removal of residual copper using a Chelex resin following previously published methods, 23,43 the polymers were dissolved in ethanol and molecular-grade water. Residual copper was measured using a colorimetric assay that detects Cu 2+ ions, and the assay results (copper ions in μg/dL) were normalized to provide mg of copper per mg of polymer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MnPEGDB Is Complexed with Small Oligonucleotides (dsDNA or siRNA) for 30 min in a pH 4 Buffer a a The protonated amine group on the DMAEMA electrostatically interacts with the negative phosphates on the oligonucleotide, spontaneously forming a stable micelle with mannose presented on the corona of the polyplex. After fabrication of the MnPEGDB and removal of residual copper using a Chelex resin following previously published methods, 23,43 the polymers were dissolved in ethanol and molecular-grade water. Residual copper was measured using a colorimetric assay that detects Cu 2+ ions, and the assay results (copper ions in μg/dL) were normalized to provide mg of copper per mg of polymer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After fabrication of the MnPEGDB and removal of residual copper using a Chelex resin following previously published methods, , the polymers were dissolved in ethanol and molecular-grade water. Residual copper was measured using a colorimetric assay that detects Cu 2+ ions, and the assay results (copper ions in μg/dL) were normalized to provide mg of copper per mg of polymer.…”
Section: Resultsmentioning
confidence: 99%
“…The following kits were used as primary antibodies for immunocytostaining: (i) cell nuclei stain Hoechst 33342 (1:100) (2′-[4-ethoxyphenyl]-5-[4-methyl-1-piperazinyl]-2,5′-bi-1 H -benzimidazole trihydrochloride trihydrate, commercialized by Dojindo, Kumamoto, Japan), (ii) mouse anti-OPPC (dilution 1:500) (Cosmo Bio Company, Tokyo, Japan), and (iii) EdU (5-ethynyl-2′-deoxyuridine; Molecular Probes, Invitrogen, Thermo Fisher Scientific, Tokyo, Japan), which was covalently incorporated into DNA as a mimic of thymidine in order to visualize the cell nucleus. The terminal alkyne group was reacted with fluorescent azide in the major groove of the double helix (Alexa568-azide under Cu­(I)-catalyzed under click reaction conditions). , Immunoassaying was visualized by means of confocal laser scanning microscopy (FV1000, Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The terminal alkyne group was reacted with fluorescent azide in the major groove of the double helix (Alexa568-azide under Cu(I)-catalyzed under click reaction conditions). 5,42 Immunoassaying was visualized by means of confocal laser scanning microscopy (FV1000, Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, in order to improve the specificity and to facilitate cellular penetration, the high affine TINA-TFOs (antiparallel and parallel types) have been conjugated to pyrrole-imidazole polyamide minor groove binders (MGB). However, it was shown that the MGBs, as part of the conjugates, do not affect the binding properties of the parent TINA-TFOs [ 215 ].…”
Section: Agents For Targeting Of Dsdnasmentioning
confidence: 99%